1981
DOI: 10.1111/j.2044-8325.1981.tb00050.x
|View full text |Cite
|
Sign up to set email alerts
|

The psychosocial impact of a labour dispute

Abstract: As a by‐product of a larger investigation, this paper examines the psychosocial impact of a 1976 labour dispute among Canadian air traffic controllers. Questionnaires were administered to the controllers during the dispute and during two subsequent periods of routine operations, four and 10 months later. The level of distress, as measured by the 30‐item General Health Questionnaire, was significantly higher during the dispute than during routine operations. The labour dispute was also accompanied by deteriorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 0 publications
2
30
0
Order By: Relevance
“…However, it is useful to have confirmed by empirical methods the data of common sense. The results also support the findings of the small amount of existing literature (i.e., MacBride et al 1981; Barling and Milligan, 1987) that found unfavourable changes in psychological well-being for those involved in an industrial dispute. However, the current study extends those findings in two important ways.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, it is useful to have confirmed by empirical methods the data of common sense. The results also support the findings of the small amount of existing literature (i.e., MacBride et al 1981; Barling and Milligan, 1987) that found unfavourable changes in psychological well-being for those involved in an industrial dispute. However, the current study extends those findings in two important ways.…”
Section: Discussionsupporting
confidence: 90%
“…Although the controllers had voted to strike, they were prevented from doing so by federal government legislation passed before the strike commenced. MacBride et al (1981), using the 30-item General Health Questionnaire to measure mental health, found that the level of psychological distress was significantly higher during the dispute than when measured 4 and 10 months later. The dispute was also accompanied by deterioration in perceived general functioning, perceived physical health and perceived anxiety.…”
Section: The Psychological Impact Of Strikesmentioning
confidence: 92%
“…Indeed, the acute cases generally took more absence than the chronic cases. Looking at those who were well at both assessments (tables 9 and 10), women Jenkins 26 (54-1) took more absence than men but both sexes increased their absence when ill. The sex difference, however, particularly in certified absence, was reversed in those who were ill at both assessments: chronically ill men take more absence than chronically ill women.…”
Section: Association Of Minor Psychiatric Morbidity With Sickness Absmentioning
confidence: 99%
“…Breakdowns in the labour-management relationship represent a further source of W stress. Macbride, Lancee, and Freeman (1981) and Barling and Milligan (1987) showed that involvement in labour disputes and/or strikes exerts a detrimental effect on subsequent psychological well-being.…”
mentioning
confidence: 99%